Indebted How Families Make College Work at Any Cost. - Zaloom, Caitlin (Princeton University Press, 2021)
How the financial pressures of paying for college affect the lives and well-being of middle-class families The struggle to pay for college is a defining feature of middle-class life in America. Caitlin Zaloom takes readers into homes of families throughout the nation to reveal the hidden consequences of student debt and the ways that financing college has transformed our most sacred relationships. She describes the profound moral conflicts for parents as they try to honor what they see as their highest parental duty-providing their children with opportunity-and shows how parents and students alike are forced to gamble on an investment that might not pay off. Superbly written and unflinchingly honest, Indebted breaks through the culture of silence surrounding the student debt crisis, exposing the unspoken costs of sending our kids to college.